Public and Private Sector Approaches to Improving Pharmaceutical Quality in Bangladesh - Bumpas, Janet (World Bank, Washington, DC, 2021)
Low-cost high-quality drugs benefit society and improve pharmaceutical company's competitive edge. This study presents the issues that must be considered to achieve these common objectives in Bangladesh. This is not a policy paper outlining exact recommendations; rather it is a discussion paper which explores the field and points towards options for Government and the local industry. Previous efforts to improve the drug quality in Bangladesh focused without much success on stricter regulation of the public market. This paper addresses this issue from a more private sector approach. The existing quality and price of pharmaceuticals are analyzed and alternative mechanisms are explored to improve the quality and cost competitiveness of Bangladesh's pharmaceuticals domestically and internationally. This paper also examines two external forces currently impacting Bangladesh's pharmaceutical sector which can provide opportunities for change. The first is World Trade Organization's (WTO)'s Trade Related Aspects of Intellectual Property (TRIPS), which grants Bangladesh domestic manufacturing opportunities and limited export advantages. Pursuing TRIPS opportunities must be carefully considered for the following reasons: they are time sensitive, require up-front investments, are likely influenced by international political pressures, provide unclear benefits, and China and India, the world leaders in low-cost pharmaceutical manufacturing, and are still extremely competitive. This paper concludes with policy and institutional suggestions for Government to improve the price and quality competitiveness of Bangladesh's pharmaceuticals. The recommendations are targeted at improving the domestic market, increasing export potential and taking advantage of TRIPS. The conclusions are preliminary and more analysis is suggested.